Genital ulcer disease in men in Durban, South Africa. Issue 4 (August 1991) - O'Farrell, N; Hoosen, A A; Coetzee, K D; van den Ende, J
Abstract : OBJECTIVE–To study the microbial aetiology of genital ulcer disease (GUD) in men. DESIGN–Microbiological and clinical assessment of genital ulcers in men. SETTING–City Health sexually transmitted diseases clinic, King Edward VIII Hospital, Durban, South Africa. PARTICIPANTS–100 Zulu men with genital ulcers who had not received antibiotics in the previous four weeks. RESULTS–Syphilis was diagnosed in 42%, chancroid in 22%, donovanosis (granuloma inguinale) in 11%, genital herpes in 10% and lymphogranuloma venereum (LGV) in 6%. No pathogens were identified in 24%. Mixed infections were detected in 14 men, in whom 13 had syphilis. Five men had HIV-1 antibodies. Neisseria gonorrhoeae was isolated from the ulcers and urethra in seven men and from the urethra alone in five. Scabies was diagnosed clinically in eight. CONCLUSIONS–All the major causes of GUD are prevalent in Zulu men in Durban. Primary syphilis was the commonest and was invariably present in mixed infections. Donovanosis was under-reported and was associated with a long delay before presentation. In this population, genital ulcers other than superficial lesions should be treated with anti-syphilitic therapy and oral antibiotics effective against chancroid and donovanosis.